Knowledge and Practice on Infection Prevention among Nurses of Bir Hospital, Kathmandu - Shrestha, Goma Niraula; Thapa, Bandana (Journal of Nepal Health Research Council, 2018)
Background: Infection prevention is a crucial component to provide quality care in any health care setting. Infections are leading cause of death and preventable illness. This study was conducted to find out the knowledge and practice among nurses regarding infectionprevention.Methods: A descriptive study design was adopted for the study. Total 170 nurses were included by usingcensus technique to assess knowledge on infection prevention.Probability systematic sampling technique was used by selecting every odd number from staffs’ list to observe the practice of 85 nurses..Semi-structured self-administered questionnaire and observation checklist was used for data collection.Results: The study showed that 57.1% of respondents had adequate knowledge and only 48.2% had good practice on infection preventionthrough hand hygiene, use of adequate personal protective equipment, decontamination, cleaning of instruments, sterilization, and use of antiseptics, disposal of sharps and waste disposal. Similarly 88.8% of the respondents had not received any training related to infection prevention.Conclusions: This study reveals that respondents had better knowledge than practice on infection prevention. The study suggestthat need for organizing regular training, monitoring, development and implementation of guideline to improve knowledge and practice of nurses for prevention of infection in the hospital.